The Effect of the Mental Drama Strategy on Developing Creative Imaginative Skills in Oral Expression Among Second-Year Female Students at the Institute of Fine Arts (Journal of the College of Basic Education, 2026)
This study aims to investigate the effect of the Mental Drama Strategy on developing creative imagination skills in oral expression among female secondary school students at the Institute of Fine Arts. The research problem stemmed from an observed weakness in students’ ability to generate creative ideas and imaginative visualizations during oral expression. The study adopted a quasi-experimental design with two groups (experimental and control) using pre- and post-tests. The sample consisted of (??) students randomly selected from the research population. The experimental group was taught using the Mental Drama Strategy, while the control group was taught through traditional methods.The results revealed statistically significant differences at the (0.05) level between the mean scores of the two groups in the post-test, favoring the experimental group. This indicates the effectiveness of the Mental Drama Strategy in enhancing creative imagination and oral expression skills. The study recommends integrating drama-based mental simulation strategies into Arabic language curricula and classroom activities, and conducting further studies on other educational stages and various language skills.